The clueless girl's guide to being a genius - Repka, Janice (New York : Dutton Children's Books, 2011)
When Aphrodite Wigglesmith, a thirteen-year-old, Harvard-educated mathematics genius, returns home to teach remedial math to middle school students, both she and her students end up getting unexpected lessons.
Kirkus Review
Kirkus Review, July 2011
4.3
3-6
3-6
Keywords: Baton twirling -- Juvenile fiction; Genius -- Juvenile fiction; Mathematics -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Teachers -- Juvenile fiction; Baton twirling -- Fiction; Genius -- Fiction; Mathematics -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Teachers -- Fiction; Baton twirling -- Fiction; Genius -- Fiction; Mathematics -- Fiction; Middle schools -- Fiction; School stories; Teachers -- Fiction